Perencanaan desain reaktor biodiesel sistem batch untuk produksi biodiesel skala industri kecil - Shofiatul Ula; Fadwah Maghfurah; Syarif Abdullah; Aditiyo Hermawan (TURBO [Tulisan Riset Berbasis Online], 2019)
Recently biodiesel production is produced by large industries. In order to be produced by small industries, the biodiesel production process requires good design which will affect the cost and yield of production. This research aims to make a batch system biodiesel reactor design and find out what materials are used in order to produce small-scale industrial biodiesel. This research is expected to provide small-scale industrial biodiesel production opportunities and the industry able to produce fuel independently. The batch system biodiesel reactor that has been designed production capacity of 144 liters each day. It has the following specifications: consists of 2 volume tubes each of which 38.2 liters with stainless steel material and 2 volume tubes of 38.2 liters each with plastic material HDPE motor power is 260 Kw, shaft diameter 20 mm, pulley length 134 cm using type A, the stirring process uses bevel gear, and the type of gear used is cold dipped steel and S45C steel material. Keywords: design reactor, biodiesel, batch system, small-scale industry